PERSPEKTIF GENDER SUKU OSING DI BANYUWANGI DALAM PENILAIAN KEMANFAATAN TANAMAN - Budi Prasetyo; Tatik Chikmawati; Eko Baroto Walujo; Ervizal A.M Zuhud (Research Center for Biology-Indonesian Institute of Sciences, 2019)
The different roles and responsibilities of male and female of the Osing tribe influence the knowledge of the use of plants. The aims of research is to analyze the values of the benefits of plants based on gender perception. The research used a qualitative and quantitative methods. Data collection for the value of plant species utilization were carried out using Pebble Distribution Method (PDM) and analysis used Index of Cultural Significance (ICS). The Osing community recognised 86 plant species that were grouped in to eight beneficial groups. The male in three villages have a better understanding of ethnobotanical knowledge and practice than female on crops as staple foods, medicines, fruits, and firewood, while understanding of ornamental plants are relatively the same for both male and female. Female have a broader and more detailed understanding on vegetables, plant species used as building construction, and traditional rituals. The high PDM value in eight beneficial groups was supported by the high value of each ICS.